Asymptotic properties of $M$-estimates of parameters in a nonlinear regression model with discrete time and singular spectrum - Ivanov, O. V.; Orlovs’kyi, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study a nonlinear regression model with discrete time and observations errors whose spectrum is singular. Sufficientconditions are obtained for the consistency, asymptotic uniqueness and asymptotic normality of the $M$-estimates of theunknown parameters.